Five new species of Lamiogethes Audisio & Cline from China (Coleoptera: Nitidulidae: Meligethinae) - Liu, Meike; Yang, Xingke; Huang, Min; Cline, Andrew Richard; Sabatelli, Simone; Audisio, Paolo (Zootaxa, 2020)
Five new species of the genus Lamiogethes Audisio & Cline are described from western, central and southern China: L. falcatus sp. n. (Sichuan), L. hastipenis sp. n. (Hubei), L. sagittalis sp. n. (Shaanxi), L. unditibiis sp. n. (Chongqing), and L. limaelytralis sp. n. (Sichuan). The first four new species appear to be morphologically related to Lamiogethes ancestor (Kirejtshuk, 1980) (comb. n.) from Central China, and allied taxa. Lamiogethes limaelytralis sp. n. appears to be more isolated, probably with relationships to the recently described L. forcipenis Liu, Huang, Cline & Audisio, 2017 and L. convexistrigosus Liu, Huang, Cline & Audisio, 2017 from Sichuan. All new species differ from other closely related taxa by details of the body shape and color, as well as the shape of the male and/or female genitalia.